2023
DOI: 10.1021/acs.chemrev.2c00724
|View full text |Cite
|
Sign up to set email alerts
|

Metal Stereogenicity in Asymmetric Transition Metal Catalysis

Abstract: Chiral transition metal catalysts represent a powerful and economic tool for implementing stereocenters in organic synthesis, with the metal center providing a strong chemical activation upon its interaction with substrates or reagents, while the overall chirality of the metal complex achieves the desired stereoselectivity. Often, the overall chiral topology of the metal complex implements a stereogenic metal center, which is then involved in the origin of the asymmetric induction. This review provides a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 291 publications
0
17
0
Order By: Relevance
“…DFT calculations of the iodide-bound catalyst implicate a Curtin–Hammett-type scenario in which the transition states for aldehyde coordination from an equilibrating mixture of sec - and tert -prenylruthenium complexes are rate- and product-determining. These studies, which underscore the profound influence of both halide counterions and metal-centered diastereo­selectivity vis-à-vis selectivity in metal catalysis, have unlocked a practical method for catalytic enantio­selective carbonyl tert -prenylation mediated by the abundant feedstock diene isoprene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations of the iodide-bound catalyst implicate a Curtin–Hammett-type scenario in which the transition states for aldehyde coordination from an equilibrating mixture of sec - and tert -prenylruthenium complexes are rate- and product-determining. These studies, which underscore the profound influence of both halide counterions and metal-centered diastereo­selectivity vis-à-vis selectivity in metal catalysis, have unlocked a practical method for catalytic enantio­selective carbonyl tert -prenylation mediated by the abundant feedstock diene isoprene.…”
Section: Resultsmentioning
confidence: 99%
“…Halide counterions can profoundly influence metal-catalyzed reactions, yet the precise nature of their effect is seldom understood . In recent work, experimental and computational analyses of the halide-bound ruthenium-JOSIPHOS complexes, RuX­(CO)­(η 3 -C 3 H 5 )­(JOSIPHOS), where X = Cl, Br, and I, revealed that the enhanced enantio­selectivities of iodide-containing catalysts emanate from iodide’s capacity to promote selective formation of a chiral-at-ruthenium octahedral stereocenter , and engage in formyl CH···I hydrogen bonding in the transition state for carbonyl addition . By exploiting iodide counterions in combination with C 1 -symmetric JOSIPHOS ligands, the intervention of predominantly one of 10 possible diastereomeric transition structures could be achieved, enabling highly enantio­selective ruthenium-catalyzed 1-aryl-1-propyne-mediated carbonyl (α-aryl)­allylations, 2-butyne-mediated carbonyl vinylations, and butadiene/methylallene-mediated crotylations (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[5] The chirality of these complexes originates from a helical cis-arrangement of two bidentate ligands in an octahedral coordination sphere, thereby generating a stereogenic Λ (left-handed helicity) or Δ (right-handed helicity) metal center as the exclusive stereocenter in these complexes (chiral-at-iron catalysts). [6][7][8] Beyond the generation of a stereogenic metal center from the helical arrangement of two inert bidentate ligands complemented by two labile monodentate ligands (2 + 2 + 1 + 1 system), we recently became interested in the generation of a stereogenic center from the coordination of one inert meridional tridentate, [9] one inert bidentate and one labile monodentate ligand in an octahedral coordination sphere (3 + 2 + 1 system), [10] which generates a stereogenic metal center in case the tridentate ligand is unsymmetric (Figure 1a, c ¼ 6 e). Such chiral (3 + 2 + 1) systems are underexplored for applications in asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Ideal enantioselective olefin metathesis should generally achieve both high enantioselectivity for the generated chiral elements and high stereoselectivity ( Z - or E -selectivity) for the formed double bonds. Molybdum (Mo)- and ruthenium (Ru) -based catalysts have been developed for three major enantioselective olefin metatheses: asymmetric ring-opening/cross-metathesis (AROCM), asymmetric ring-closing metathesis (ARCM), and asymmetric cross-metathesis (ACM). Although Ru-based catalysts still cannot achieve the same high level of enantioselectivity as early transition metal-based catalysts at present, their stability to air and moisture, as well as their excellent functional group tolerance, makes their development and application appealing to the synthetic community…”
Section: Introductionmentioning
confidence: 99%